On the uniqueness of a solution of the problem with oblique derivative for the equation Δ n v = 0 - Kapanadze, D. V. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
We prove the uniqueness of a solution of the problem with oblique derivative for the equation Δ n v = 0.